The needs and unmet needs for people living with dementia, caregivers and care workers in dementia health care systems: a systematic review - Michele Sorrentino; Michele Sorrentino; Michelangelo Mercogliano; Claudio Fiorilla; Irene Stilo; Federica Esposito; Marcello Moccia; Marcello Moccia; Luigi Lavorgna; Giuseppina Affinito; Elena Salvatore; Maria Pia Sormani; et al. (Frontiers in Public Health)
IntroductionThe prevalence and costs of dementias are rising due to demographic changes. Dementia care depends largely on informal caregivers and fragmented healthcare systems that often fail to meet the needs of people with dementia.ObjectivesThis systematic review aims to identify unmet needs and barriers in European dementia care, providing a framework to improve health strategies.MethodsFollowing PRISMA guidelines, articles from 2013 to 2023 were screened from Embase, PsycINFO, HTA Database, and Web of Science. The Mixed Methods Appraisal Tool was used for evaluation.ResultsFrom 3,738 articles, 47 met the inclusion criteria. Through a narrative synthesis, the review identified unmet needs and barriers among People Living with Dementia, caregivers, and healthcare workers. Psychosocial and emotional support are essential for managing stress and ensuring quality of life. Caregivers demand education about dementia care, progression, and self-care, while healthcare workers need training, and interdisciplinary teams. Cultural sensitivity is critical for addressing stigma and facilitating inclusive care for ethnic minorities. Healthcare access remains fragmented, thereby decreasing continuity of care for families. High costs, bureaucratic complexity, and geographical inequalities, particularly in rural areas can be barrier to care for People Living with Dementia and their families. The COVID-19 pandemic disrupted social support services, increasing distress and uncertainty. About limitation, publication bias and geographical bias from focus on Europe were possible, potentially overlooking insights from other regions.ConclusionThere is need for public policies to enhance education, community support, and dementia awareness, with a focus on culturally sensitive care.